A Short‐Chain Branching Distribution Determination Technique for Polyethylene Using IR5‐Detected GPC. Issue 1 (27th April 2020) - Yu, Youlu
Abstract: In this paper, a robust short‐chain branching (SCB) determination technique recently developed using IR5‐detected GPC (GPC‐IR5) for polyethylene resins is reported, wherein the IR5 detector is an infrared detector equipped with five filters set at different frequency ranges and a mercury‐cadmium‐telluride detector with thermoelectric cooling capability. Both intensity ratios of methyl/methylene and methyl/all C─H groups have very good linear relationship with the SCB content. Based on these relationships, an excel spreadsheet method is developed to deduce the SCB distribution across the molecular weight distribution using in‐house developed algorithms. The uncertainty of SCB determination using the GPC‐IR5 technique is found to be chromatographic signal‐to‐noise ratio dependent and can be explicitly expressed and calculated slice by slice. The SCB uncertainty is also found to be a function of experimental conditions and environment, which can affect not only the signals but also the noise levels at different IR bands. At a given polymer concentration, the higher the SCB content, the smaller the relative error bars. The SCB detection limit of this GPC‐IR5 technique is found to be at ≈0.5–1.0 SCB per 1000 TC for all samples tested. Some practical aspects for application of this technique are also discussed in this paper.